2019
DOI: 10.2147/ijn.s217977
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multi-Walled Carbon Nanotubes (MWCNTs) Activate Apoptotic Pathway Through ER Stress: Does Surface Chemistry Matter?</p>

Abstract: PurposePhysicochemical properties play a crucial role in determining the toxicity of multi-walled carbon nanotubes (MWCNTs). Recently we found that MWCNTs with longer length and smaller diameters could induce toxicity to human umbilical vein endothelial cells (HUVECs) through the activation of endoplasmic reticulum (ER) stress. In this study, we further investigated the possible contribution of hydroxylation and carboxylation to the cytotoxicity of MWCNTs.MethodsThe HUVECs were exposed to pristine (code XFM19)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…17,23 These results indicated that unmodified and carboxylated MWCNTs were equally cytotoxic to THP-1 macrophages. Previous studies also reported that unmodified and carboxylated MWCNTs were equally cytotoxic to human endothelial cells, 24 THP-1 macrophages, 21 vascular smooth muscle cells, 25 and HepG2 cells, 26 although MWCNTs used in previous studies contained a much lower level of carboxyl groups compared with the MWCNTs used in this study (1.23 wt% vs 3.86 wt%). Hereby, our results indicated that even a relatively high degree of carboxylation did not change the cytotoxic potential of MWCNTs to THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 42%
“…17,23 These results indicated that unmodified and carboxylated MWCNTs were equally cytotoxic to THP-1 macrophages. Previous studies also reported that unmodified and carboxylated MWCNTs were equally cytotoxic to human endothelial cells, 24 THP-1 macrophages, 21 vascular smooth muscle cells, 25 and HepG2 cells, 26 although MWCNTs used in previous studies contained a much lower level of carboxyl groups compared with the MWCNTs used in this study (1.23 wt% vs 3.86 wt%). Hereby, our results indicated that even a relatively high degree of carboxylation did not change the cytotoxic potential of MWCNTs to THP-1 macrophages.…”
Section: Discussionmentioning
confidence: 42%
“…Many studies report that mild hyperthermia (42–45 °C) is optimal to induce apoptosis via mitochondrial damage and oxidative stress. Higher temperatures (≥52 °C) could damage normal cells and increase PTT adverse effects [ 64 , 65 ]. As a matter of fact, cell necrosis is temperature-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Acknowledging this, we first examined the in vitro toxicity of DSPE-PEG (5000) amine SWCNTs in vital organs including the liver and lungs. It is necessary to check if the concentrations of these nanomaterials are safe to be used in future biomedical applications or not [ 61 , 62 , 65 , 66 ]. The molecular weight and functional group charges of DSPE-PEG were assumed to play an important role in the biocompatibility improvement of DSPE-PEG amine SWCNTs [ 45 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Direct contact of endothelial cells with NMs, such as carbon nanotubes (Y. Sun, Gong, & Cao, 2019; X. Zhao et al, 2019), CB NPs (G. Wang et al, 2019), ZnO NPs (Chen et al, 2014), TiO 2 NPs (Simon et al, 2017), and CdTe QDs (M. Yan et al, 2016), activated ER stress as the mechanism to induce cytotoxicity. In this study, we also found that CB NPs induced ER stress–apoptotic proteins (Figure 5), which could explain the cytotoxicity of CB NPs to HUVECs.…”
Section: Discussionmentioning
confidence: 99%